Jigsaw Cooperative Learning to Improve Critical Reading Skills - Afore Tahir Harefa (Universitas Muhammadiyah Enrekang, 2020)
This research aims to analyze (1) the design of learning planning for critical reading comprehension of English through jigsaw-type cooperative learning in Critical reading courses; (2) the implementation of learning the understanding of critical reading of English through jigsaw type cooperative learning in critical reading courses; (3) the evaluation system of learning critical reading comprehension of English through jigsaw type cooperative learning; and (4) improved students' critical English reading comprehension skills through jigsaw-type cooperative learning on Critical reading courses. The research method used is Classroom Action Research which is carried out in three cycles. The subject of this study is students who take Critical Reading courses in the even semester of 2020. The data collection techniques used in this study are assessment sheets, observations, and tests. The data analysis used is the analysis of description. The conclusions of this study are (1) the learning design used in preparing the lesson plan is ASSURE. The preparation of SAP in critical reading learning is based on competency standards, basic competencies, indicators, learning objectives, subject matter, methods, and sources, as well as a cooperative learning approach consisting of four activities, namely critical reading, expert group discussions, home group discussions, and quizzes; (2) the implementation of learning is an activity carried out by students and lecturers in learning critical reading comprehension using jigsaw type cooperative learning. The observed student activities include activeness, attention, cooperation, and responsibility. Lecturer activities observed include lecturer activities from preliminary activities, presentation and closing of learning; (3) the evaluation system is the result of analysis of critical reading comprehension questions in the form of multiple choices with four choices using an interest which includes validity, reliability, discriminatory power, and level of difficulty of the questions, and; (4) Jigsaw cooperative learning can improve critical reading comprehension skills, namely the ability of students to understand and answer questions about the basics of critical reading comprehension and the ability to conclude reading or text content.